Optical Clearing and Light Sheet Microscopy Imaging of Amphioxus - Machacova, Simona; Chmelova, Helena; Vavrova, Anna; Kozmik, Zbynek; Kozmikova, Iryna (Frontiers in Cell and Developmental Biology, 2021)
Cephalochordates (amphioxus or lancelets) are representatives of the most basally divergent group of the chordate phylum. Studies of amphioxus development and anatomy hence provide a key insight into vertebrate evolution. The more widespread use of amphioxus in evo-devo field would be greatly facilitated by expanding the methodological toolbox available in this model system. For example, evo-devo research on amphioxus requires a deep understanding of animal anatomy. Although the conventional confocal microscopy can visualize transparent amphioxus embryos and early larvae, the imaging of later developmental stages is problematic because of the size and opaqueness of the animal. Here, we show that light sheet microscopy combined with tissue clearing methods enables exploration of large amphioxus specimens while keeping the surface and the internal structures intact. We took advantage of the phenomenon of autofluorescence of amphioxus larva to highlight anatomical details. In order to investigate molecular markers at a single-cell level, we performed antibody-based immunodetection of melanopsin and acetylated-α-tubulin to label rhabdomeric photoreceptors and the neuronal scaffold. Our approach that combines light sheet microscopy with the clearing protocol, autofluorescence properties of amphioxus, and antibody immunodetection allows visualizing anatomical structures and even individual cells in the three-dimensional space of the entire animal body.